Outcomes of Halo Immobilization for Cervical Spine Fractures. Issue 5 (August 2019) - Isidro, Stacey; Molinari, Robert; Ikpeze, Tochukwu; Hernandez, Cesar; Mahmoudi, Mohamed Salah; Mesfin, Addisu
Study Design: Retrospective. Objectives: To evaluate complications and outcomes of halo immobilization in patients with cervical spine fractures treated at a level I trauma center. Methods: A retrospective evaluation of patients treated at a single institution with halo immobilization from August 2000 to February 2016 was performed. Demographic information, mechanism of injury, level and type of spine fracture, length of halo immobilization, complications associated with halo immobilization, and length of patient follow-up were collected. Results: A total of 189 patients treated with halos were identified. Of the 189 patients, 121 (64%) received halos for the management of cervical spine fractures and were included in the study. A total of 49.6% were males and 50.4% were females. The average age was 50.8 years (range 1-89 years). Overall, 10.7% sustained C1 fractures, 71.1% C2 fractures, and 18.2% subaxial spine (C3-C7) fractures. In all, 47.1% of the upper cervical fractures were either odontoid or hangman-type fractures. A total of 25.1% of patients had multiple cervical fractures. At latest follow-up, 81% had healed fractures with good alignment, minimal pain, and return to normal activities. There was an 8.3% mortality rate. The mortality group had an average age of 64.7 years (range 19-84 years). A total of 10.7% of patients failed halo immobilization and 46.3% of patients had complications such as pin site infections (5.8%), loose pins (1.7%), neck pain (20.7%), decreased range of motion (14%), thoracic skin ulcers (2.4%), and dysphagia (1.7%). Conclusions: The use of halo immobilization for cervical spine fractures resulted in clinical success in 81% of patients. Complication rates in geriatric patients were lower than previously reported in the literature.